Pharmacological evidence of bradykinin regeneration from extended sequences that behave as peptidase–activated B2 receptor agonists - Charest-Morin, Xavier; Roy, Caroline; Fortin, Émile-Jacques; Bouthillier, Johanne; Marceau, François (Frontiers in Pharmacology, 2014)
While bradykinin (BK) is known to be degraded by angiotensin converting enzyme (ACE), we have recently discovered that Met-Lys-BK-Ser-Ser is paradoxically activated by ACE. We designed and evaluated additional “prodrug” peptides extended around the BK sequence as potential ligands that could be locally activated by vascular or blood plasma peptidases. BK regeneration was estimated using the contractility of the human umbilical vein as model of vascular functions mediated by endogenous B2 receptors (B2Rs) and the endocytosis of the fusion protein B2R-green fluorescent protein (B2R-GFP) expressed in HEK 293 cells. Of 3 BK sequences extended by a C-terminal dipeptide, BK-His-Leu had the most desirable profile, exhibiting little direct affinity for the receptor but a significant one for ACE (as shown by competition of [3H]BK binding to B2R-GFP or of [3H]enalaprilat to recombinant ACE, respectively). The potency of the contractile effect of this analog on the vein was reduced 18-fold by the ACE inhibitor enalaprilat, pharmacologically evidencing BK regeneration in situ. BK-Arg, a potential substrate of arginine carboxypeptidases, had a low affinity for B2Rs and its potency as a contractile agent was reduced 15-fold by tissue treatment with an inhibitor of these enzymes, Plummer’s inhibitor. B2R-GFP internalization in response to 100 nM of the extended peptides recapitulated these findings, as enalaprilat selectively inhibited the effect of BK-His-Leu and Plummer’s inhibitor, that of BK-Arg. The 2 peptidase inhibitors did not affect BK-induced effects in either assay. The novel C-terminally extended BKs had no or very little affinity for the kinin B1 receptor (competition of [3H]Lys-des-Arg9-BK binding). The feasibility of peptidase-activated B2R agonists is illustrated by C-terminal extensions of the BK sequence.